1989
DOI: 10.1111/j.2044-8260.1989.tb01376.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of WAIS IQ with the National Adult Reading Test: Cross‐validation and extension

Abstract: Nelson (1982) presented regression equations for the prediction of Wechsler Adult Intelligence Scale (WAIS) IQ from performance on the National Adult Reading Test (NART). In a cross‐validation sample (n = 151) these equations predicted 66, 72 and 33 per cent of the variance in WAIS Full Scale, Verbal and Performance IQ respectively. There were no ceiling or floor effects in the relationship between NART performance and WAIS IQ despite the wide IQ range of the sample. The standardization and cross‐validation sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 4 publications
5
112
0
Order By: Relevance
“…It is possible that reading scores in participants with dementia lowered the mean scores in our sample (Patterson et al, 1994;Storandt et al, 1995;Taylor et al, 1996); however, the vast majority of dementia cases in our sample were mild (13 of 14), and many studies have suggested that single word reading is preserved in early dementia (Crawford et al, 1989;Del Ser et al, 1997;Hart et al, 1986;Nelson & O'Connell, 1978;O'Carroll & Gilleard, 1986;Sharpe & O'Carroll, 1991). Importantly, the proportion of individuals with dementia in our sample did not differ by ethnicity or language, suggesting that any potential effect of cognitive impairment on the current data would not vary across group.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…It is possible that reading scores in participants with dementia lowered the mean scores in our sample (Patterson et al, 1994;Storandt et al, 1995;Taylor et al, 1996); however, the vast majority of dementia cases in our sample were mild (13 of 14), and many studies have suggested that single word reading is preserved in early dementia (Crawford et al, 1989;Del Ser et al, 1997;Hart et al, 1986;Nelson & O'Connell, 1978;O'Carroll & Gilleard, 1986;Sharpe & O'Carroll, 1991). Importantly, the proportion of individuals with dementia in our sample did not differ by ethnicity or language, suggesting that any potential effect of cognitive impairment on the current data would not vary across group.…”
Section: Discussionmentioning
confidence: 64%
“…Further, prior studies of the WAT (Del Ser et al, 1997) and NART (Crawford et al, 1989;Nelson & O'Connell, 1978) have demonstrated comparable reading scores across healthy controls and patients with mild AD, and such scores have been shown to remain stable over time in the context of cognitive decline associated with mild AD (Hart et al, 1986;O'Carroll & Gilleard, 1986;Sharpe & O'Carroll, 1991). However, to be sure that the presence of dementia in one group did not systematically bias our findings, we analyzed the proportion of individuals with this diagnosis across ethnic and language group.…”
Section: Subjectsmentioning
confidence: 94%
See 1 more Smart Citation
“…Before analysis, test scores were converted into Tscores (mean of 50 and a standard deviation [SD] of 10) that were age-corrected for the WAIS-III and WMS-III measures, 18,20 and age-and education-corrected for the CVLT, 17 Trail Making, 25 Finger Oscillation Test, 19 and COWA. 21 A total neuropsychologic score was created by averaging performance across all measures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that performance on the NART is highly correlated with general intelligence (factor 'g') as measured by the Wechsler intelligence scales. 18 Accordingly, NART was included to estimate overall intellectual ability and was not combined with scores from the other cognitive measures.…”
Section: Cognitive Performancementioning
confidence: 99%